2015
DOI: 10.1212/01.con.0000466658.05156.54
|View full text |Cite
|
Sign up to set email alerts
|

Executive Dysfunction

Abstract: Purpose of Review: Executive functions represent a constellation of cognitive abilities that drive goal-oriented behavior and are critical to the ability to adapt to an ever-changing world. This article provides a clinically oriented approach to classifying, localizing, diagnosing, and treating disorders of executive function, which are pervasive in clinical practice. Recent Findings: Executive functions can be split into four distinct components: working memory, inhibition, set shifting, and fluency. These co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
98
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(106 citation statements)
references
References 42 publications
(33 reference statements)
4
98
1
3
Order By: Relevance
“…All results depicted were significant at a corrected level (P FWE <.05). [Color figure can be viewed at wileyonlinelibrary.com] patterns; Favorites correlated with brain regions important for memory, including the medial temporal lobes 20 ; Match correlated with brain regions important for executive functions and speed in the dorsal frontoparietal network and basal ganglia 21 ; and Line Orientation correlated with a cluster in the right parietal lobe. 22 The remaining BHA cognitive subtest, Animal Fluency (widely used to assess the language domain), is sensitive to temporal and frontal lobe pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…All results depicted were significant at a corrected level (P FWE <.05). [Color figure can be viewed at wileyonlinelibrary.com] patterns; Favorites correlated with brain regions important for memory, including the medial temporal lobes 20 ; Match correlated with brain regions important for executive functions and speed in the dorsal frontoparietal network and basal ganglia 21 ; and Line Orientation correlated with a cluster in the right parietal lobe. 22 The remaining BHA cognitive subtest, Animal Fluency (widely used to assess the language domain), is sensitive to temporal and frontal lobe pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, the patient exhibited various patterns of damage known to systematically disrupt various domains. For example, putative associations have been established between frontostriatal lesions and motor disability (Zgaljardic et al, 2003), insulo-parietal compromise and somatosensory deficiencies (Meyer et al, 2016), bilateral fronto-insular damage and social cognition deficits (Ibáñez et al, 2010, 2016a; Couto et al, 2013; Baez et al, 2014, 2016b; Melloni et al, 2016), bilateral frontal atrophy and executive dysfunctions (Rabinovici et al, 2015), left perisylvian lesions and language impairment (Ullman, 2008), and right-sided frontal disturbances and altered pragmatic skills (Kaplan et al, 1990; Stemmer, 2008). Moreover, the regions affected should typically disrupt multiple functional networks, such as the salience network (Seeley et al, 2007), the social context network (Ibáñez and Manes, 2012; Baez et al, 2016a), and the fronto-parietal attention network (Ptak, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…These steps are critical and perhaps unavoidable to characterize the organ's functional organization with some degree of external validity. Indeed, thanks to this approach, replicable associations have been established between damage to circumscribed regions and impairments of specific functions, including motor (Zgaljardic et al, 2003), somatosensory (Meyer et al, 2016), socio-cognitive (Gold and Shadlen, 2007; Ibáñez et al, 2010, 2016b; Couto et al, 2013; Baez et al, 2014, 2016b,c; Melloni et al, 2016), interoceptive (Couto et al, 2015; García-Cordero et al, 2016), executive (Rabinovici et al, 2015; Sedeño et al, 2016), linguistic (Ullman, 2008; Cardona et al, 2014; García and Ibáñez, 2014, 2016; Bocanegra et al, 2015; García, 2015; Melloni et al, 2015; García et al, 2016a,b,c; Abrevaya et al, 2017), and pragmatic (Kaplan et al, 1990; Stemmer, 2008) skills.…”
Section: Introductionmentioning
confidence: 99%
“…The frontal cortex in association with the parietal cortex, basal ganglia, thalamus and cerebellum are involved in high-level cognitive functions such as working memory, set shifting, fluency, focused attention, episodic memory retrieval, abstract thinking, tracking alternative outcomes during decision-making and planning (Rabinovici, Stephens, & Possin, 2015). Recent experiments conducted in both human patients and animal models have demonstrated that the presence of chronic pain is closely associated with significant functional and structural modifications in different cortical regions, including the amygdala, anterior cingulate cortex, hippocampus and prefrontal cortex (Kim & Kim, 2016;Lithwick, Lev, & Binshtok, 2013).…”
Section: About Tnf-α Levels and Astrocytic Gfap Expressionmentioning
confidence: 99%